Long-term ammonia gas biofiltration through simultaneous nitrification, anammox and denitrification process with limited N2O emission and negligible leachate production. (10th October 2020) - Yan, Jia; Wang, Siji; Wu, Lingyao; Li, Shugeng; Li, Huosheng; Wang, Yu; Wu, Jiapeng; Zhang, Hongguo; Hong, Yiguo
Abstract: Ammonia is toxic and malodorous gas, which is emitted from agricultural and industrial sources. Most of known ammonia gas treatment methods share the disadvantages of expensive cost, by-product pollution and high energy consumption. In this study, an ammonia gas biotreatment method was developed, through simultaneous nitrification, anammox and denitrification process (SNAD) in a biofilter, which was expected to reduce operation cost, secondary pollution and energy consumption. Ammonia gas was converted to di-nitrogen gas (97.2–99.5%) and nitrous oxide (0.5–1.8%), with the highest ammonia loading rate of 0.173 gNH3 /gVSS·d. Removed ammonia was taken up by both nitrification (70.6%) and anammox (29.4%) process. Anammox and denitrification process contributed to about 60% and 40% of di-nitrogen gas production in SNAD system, respectively. N2 O emission might be caused by nitrification as well as denitrification processes, but not by anammox process in the reactor. TN removal efficiency achieved up to 99.4%, which suggested negligible leachate production in SNAD system for ammonia gas filtration. Anammox activity was not inhibited after introducing oxygen, which was most likely related to activity of oxygen-consuming ammonia oxidation, nitrite oxidation and denitrification. As far as know, this study is the first evidence for ammonia gas biofiltration with anammox-related technology, which might be a highly efficient and cost effective solution for ammonia gas removal with less energy consumption (<30%), biomass production (∼10%), greenhouse gas emission (70–80%) and wastewater production (100%). Graphical abstract: Image 1 Highlights: NH3 gas was treated through simultaneous nitrification, anammox and denitrification. Ammonia was effectively converted to N2 and N2 O (<1.8%) in SNAD system. N2 production was attributed to both anammox (60%) and denitrification (40%). No leachate produced in SNAD reactor due to high TN removal efficiency. Energy consumption and biomass production reduced up to 30% and 90%, respectively.